Analisis Kajian Teknis dan Ekonomis Biaya Operasional Terhadap Hasil Produksi KIP Timah 14 PT.Timah (Persero),Tbk di Laut Tempilang, Bangka Belitung - Derry Trenza Maida; Murad Murad; Yoszi Mingsi Anaperta (Journals Mining Engineering : Bina Tambang, 2015)
PT. Timah (Persero) Tbk. Bangka Marine Unit is a unit of production of PT.Timah (Persero) Tbk. which conduct mining using Dredger and Cutter Suction,one of them using the KIP TIMAH 14 operating in Tempilang Sea.This research is based on the ISO 50001 and Energy PerformanceManagement, namely by looking at the rate of fuel (HSD) consumption towardKIP Timah 14’s production, to attempt efficiency, and to make daily consumptionfunctions of HSD. Attempt efficiency is to examine two issues, the use of rightunderwater machine (Mineral Dressing Installation Activator) and excavationmethod (excavation volume reduction). From observations in the field, during theoperation of KIP Timah 14 found frequent damages in mineral dressinginstallation and excavations are not effective. From the problems above so thatattempted Efficiency by reducing the volume of excavation is not required anddoes not operate the right underwater mechine when digging overburden.After the efforts of efficiency obtained, HSD consumption savings aboutRp.536,721,972.70 in November 2014, Rp.792,734,317.80 in December 2014, andRp.644,841,956.40 in January 2015. The efforts of effeciency feasible to do inorder to suppress the mining operating costs.